2017
DOI: 10.3748/wjg.v23.i45.8044
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of liver and spleen shear wave velocity in predicting the prognosis of patients with portal hypertension

Abstract: AIMTo explore the relationship of liver and spleen shear wave velocity in patients with liver cirrhosis combined with portal hypertension, and assess the value of liver and spleen shear wave velocity in predicting the prognosis of patients with portal hypertension.METHODSAll 67 patients with liver cirrhosis diagnosed as portal hypertension by hepatic venous pressure gradient in our hospital from June 2014 to December 2014 were enrolled into this study. The baseline information of these patients was recorded. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Now it is possible to assess, in advance, the velocities in different tissues by comparing to normal controls based on large sample sizes (e.g., the cutoff value in case of a normal liver is 3.0 m/s, and normal thyroid is <2 m/s). 14,15 In the present study, a total of 141 nodules were imaged; 12 (8.5%) were found malignant, and 129 (91.5%) nodules were classified benign. Among the malignant nodules, papillary carcinoma was most common, whereas colloid goiter accounted for the majority of the benign nodules.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Now it is possible to assess, in advance, the velocities in different tissues by comparing to normal controls based on large sample sizes (e.g., the cutoff value in case of a normal liver is 3.0 m/s, and normal thyroid is <2 m/s). 14,15 In the present study, a total of 141 nodules were imaged; 12 (8.5%) were found malignant, and 129 (91.5%) nodules were classified benign. Among the malignant nodules, papillary carcinoma was most common, whereas colloid goiter accounted for the majority of the benign nodules.…”
Section: Discussionmentioning
confidence: 64%
“…Now it is possible to assess, in advance, the velocities in different tissues by comparing to normal controls based on large sample sizes (e.g., the cutoff value in case of a normal liver is 3.0 m/s, and normal thyroid is <2 m/s). 14,15…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 Similarly, some authors also found that LS can predict the presence of poor prognostic factors such as EV in patients with liver cirrhosis. 27 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…With further understanding of spleen anatomy and its immune function, increasing attention has recently been given to spleen preservation operations. Recent studies have shown that the spleen plays an important role in hepatic function protection, infection control, and tumor immunity in patients with PHT[ 2 ]. Total splenectomy in patients with liver cirrhosis reduces the ability of the body to remove particulate matter from the blood and aggravate immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%